MOLECULAR MECHANISMS OF VIRULENCE IN PHYTOPATHOGENIC FUNGI - Miranda, Giulia Stavrakas; Andrade, João Victor; de Macêdo, Adriely Valerio; Marques, Cecília Fernandes Patta Muller; Verly, Leonardo Bindelli; Rosa, Ana Carla Rangel; Macedo, Maria Eduarda Dan; Caprini, Híllary Ozorio Gobeti; Perin, Isabelle Lucas Braga; Vieira, Gabriel Finotti Alves; Santos, Mario Ferreira Conceição (Seven Editora, 2025)
Fungi are versatile organisms that play diverse ecological roles, acting as decomposers, mutualists, or plant pathogens. This chapter addresses the virulence mechanisms employed by phytopathogenic fungi, which include the adhesion and colonization of plant tissues, invasion by means of hydrolytic enzymes, and the formation of biofilms. Cellular communication via quorum sensing regulates processes such as sporulation and morphological transition, while the production of toxins and virulence factors, such as enzymes and secondary metabolites, interferes with the physiological processes of plants, facilitating infection. Fungi also develop sophisticated strategies to evade the plant immune system, such as cell wall modification and secretion of effectors that suppress defense responses. Antifungal resistance and genetic regulation of virulence are discussed, highlighting the importance of integrated control strategies, such as the use of resistant cultivars and biocontrol agents. Advanced diagnostic methods, such as PCR and next-generation sequencing, are presented as essential tools for the early detection and management of fungal diseases. DOI: https://doi.org/10.56238/sevened2025.018-036